Archaeology's Publication Problems by J. Aviram and H. Shanks - Buccellati, Giorgio (Near Eastern archaeology, 1998)
Lamentations over the condition of archaeological publication abound these days. A recent volume of essays-of distinguished provenance-rounds up the usual suspects. Yet a fundamental point is altogether missing from its discussion. What archaeologists observe and can readily document is emplacement, i.e., the cultural remains they identify in the ground. What retards publication is concentration on the depositional inferences from this record. Focusing on emplacement would both speed publication and enforce a truly essential methodological distinction.